A novel hardware Trojan detection method based on sweep‐frequency test. Issue 23 (26th September 2022) - He, Chunhua; Lei, Dengyun; Wu, Heng; Cheng, Lianglun; Huang, Qinwen; Yan, Guizhen
Abstract: This paper proposes a novel hardware Trojan detection method based on sweep‐frequency test since Trojan horse threatens information security seriously. An equivalent parasitic and load circuit model, and analysis method are depicted in detail. Experimental results of the amplitude‐frequency responses between the input and output accord with the simulation results. 11 golden chips and 9 Trojan chips are used for the sweep‐frequency tests, and the golden chips can be distinguished from Trojan chips accurately based on the relationship between the peak and valley resonant frequencies, which indicates that the proposed model and detection method are effective.